The “First Great Purge” of American Television Programming: Understanding How and Why Popular Television Changed So Dramatically from the 1950s to the 1960s - Dennis Tredy (TV Series, 2022)
Though “purge” may seem a rather dramatic choice of terms to refer to a drastic shift in the overall nature of network television programming in the United States, it has long been used by media scholars, notably in reference to “The Great Rural Purge of 1971”, when CBS suddenly decided to cancel all of its most popular, rural-based sitcoms and variety shows in exchange for a new lineup of hard-hitting, urban-based sitcoms that leaned left and dealt unapologetically with the most burning social issues of the day. This study, however, hopes to show that this shift was in fact not the first big “purge” but the second, the first having occurred circa 1957 and having moved in the exact opposite direction. One of the great misconceptions about network television is indeed that it was very conservative at its onset and grew steadily more progressive and inclusive over the decades, for pre-1957 network television and especially its comedy programs – those of the first era of the Golden Age of Television, as it were – were remarkably avant-garde and politically incorrect for their time. Anti-establishment humor, budding feminist themes (with independent women both on screen and in the writing room), racial and ethnic diversity, in-your-face insolence and transgressional humor – all of these progressive topics were showcased in very urban settings before that first “purge” erased those gains and reset the U.S. TV landscape as white, patriarchal, rural, conservative and harmlessly escapist. This study will not only discuss those breakthrough sitcoms of the early 1950s themselves, but, just as importantly, it will trace the many factors that led to that first great shift – a vast confluence of decisions and incidents that would lead to what could be dubbed “The Great Urban Purge of 1957”.